Analysis And Design Of Sales Information System Using Personal Extreme Programming (PXP) At Sumber Prima Mitra - Darmawan, Arya; Abdillah, Zakki (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
Sumber Prima Mitra currently relies on Microsoft Office such as Microsoft Word and Excel for administration and data storage purposes, as well as using Instagram and WhatsApp as communication and information media. This approach raises concerns regarding data security and the effectiveness of disseminating information about a company's products and services. This research aims to overcome this problem by designing a web-based sales information system that can increase the effectiveness of management and dissemination of information at Sumber Prima Mitra. The method applied in developing this information system is Personal Extreme Programming (PXP). PXP was chosen for its flexible and iterative approach, allowing for continuous customization according to the company's specific needs. This web-based sales information system is expected to provide an efficient platform for managing sales, marketing and promotional data. This sales information system was created using UI/UX as the basis for implementing the system. The UI/UX creation has been adjusted to the needs of Sumber Prima Mitra, so that the implementation of the system is faster and more targeted. With this system, Sumber Prima Mitra is expected to increase productivity, reduce the risk of data loss, and attract more customers through more effective and organized information dissemination.